FACTORS CONTRIBUTING TO THE ACHIEVEMENTS OF HEALTY COMMUNITY PROJECT IN SONGKHLA PROVINCE (Journal of Technology and Operations Management, 2017)
This study aimed to investigate factors contributing to the achievements of healthy community project in Songkhla Province and to explore the prioritisation of indicators which are conducive to the achievements of the project. The study revealed that the factors contributing to the achievements of the project considered in each aspect can be illustrated as follows: the factor contributing to the achievements’ mean is at 3.76. This means the factor contributing to the achievements is at a high level. This level is not agreeably congruent with what Phimainok’s study (Factors’ contributing to the accomplishment of community development based on the philosophy of the sufficient economy of Baan Namsub, Wang Nam Khiao Subdistrict, Wang Nam Khiao District of Nakhon Ratchasima) showing that one of the factors contributing to the accomplishment of the community development based on the philosophy of sufficient economy of Baan Namsub was in the aspect of supporting from the government so that trainings regarding the philosophy could be organised, financially supported, and so on. This study also disclosed that due to the difference of the context where the project was held and the project itself, the factors contributing the achievement were various. With regard to the prioritization of the indicators contributing to the healthy community project, the study showed that the project was supported by community leaders as well as by within-community organisations whose mean was at 4.0. This can signify that these supports were significant for the achievements of the project, which was at a high level. This result was in accordance with Phimainok’s study reporting that the factors which were conducive to the accomplishment of the project were that the project was both supported and sponsored by government sectors so that the trainings regarding the sufficient economic philosophy was organised.